Comparative real-world effectiveness and safety of biologics and JAK inhibitors in atopic dermatitis: short- and medium-to-long-term analysis from a regional healthcare network in southern Spain - Prados-Carmona, Alvaro; Navarro Triviño, Francisco José; Husein-ElAhmed, Husein; Ruiz-Villaverde, Ricardo (Frontiers in Medicine, 2025)
BackgroundBiologics and Janus kinase (JAK) inhibitors have expanded treatment options for moderate-to-severe atopic dermatitis (AD), but comparative real-world data remain limited.ObjectiveThis study aims to compare disease-related characteristics and outcomes of patients with moderate-to-severe AD treated with biologics or JAK inhibitors (JAKi) in routine clinical practice.Materials and methodsAn ambispective, observational study was conducted across three hospitals in southern Spain. Patients who initiated advanced systemic therapy (AST) between 2019 and 2024 were included in the study. Baseline disease-related variables, clinical severity scores, treatment outcomes, adverse events, and drug survival were assessed. Short-term (16 weeks) and medium-to-long-term (24 and 52 weeks) intervals were considered. Super-responder rates, based on a proposed definition, were also evaluated.ResultsA total of 202 patients were included (134 treated with biologics and 68 with JAK inhibitors). JAK inhibitors produced faster early responses, while biologics achieved greater absolute improvements between weeks 16 and 52, along with longer treatment persistence. The adverse event profiles differed between the drug classes: infections and acne were more common with JAKi, while ocular symptoms were more common with biologics. The difference in super-responder rates between groups was not statistically significant (16.42% vs. 23.53%, p = 0.25443).ConclusionBoth treatment classes were effective and well-tolerated. Differences in response dynamics and safety profiles support individualized treatment decisions.